celebrations and spaces - Grigoryeva, Elena; Lidin, Konstantin (project baikal, 2020)
Squares are as integral to the patterns of antique and medieval cities as holidays to the calendar. It was on the squares where rural dwellers met with urban ones during mass events and traditional agricultural holidays gradually turned into urban celebrations. Leo Salmin analyses interrelations between a European city and a celebration in their current state.Any celebration has ritual features. But is any ritual festive enough to create its own space in the urban fabric? Elena Bagina studies various examples of New Year’s celebrations.Is there room for ancient and pagan celebrations in a contemporary city? The use of ‘animal style’ in the design of present-day Perm has been debated for several years already.The 130 Quarter in Irkutsk is elongated, as if carried away by a powerful eastward movement of the state. Sandwiched in between two arterial roads, this depressive quarter with unfavorable terrain did not seem to inspire celebration ideas. However, the architects envisioned a unique universal celebration space at the intersection of human flows. To continue the discussion about the quarter, one of Irkutsk landmarks, we are publishing the article on the fate of the amphitheatre and the transformation of the square during the realization of the project.Anastasia Malko speaks about an unusual tradition of a neighborhood in Dresden. Year after year, ‘Bunte Republik Neustadt’ flourishes in this city, which has both German self-restraint and Saxonic cheerfulness. The celebration creates a space for itself with the help of the citizens.
Keywords: urban celebrations; ritual; urban fabric; space